Effect of Blended Learning on Academic Achievements and Attitude of Nursing Students: A Systematic Review - Kanika1 , Harmeet Kaur2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Technological advances have revolutionized teaching and learning processes. With the emergence of technologies and need for cost-effective teaching methods have led to the molding of teaching learning practices.Considering these constant and rapid changes, it is crucial that learners in health care area should be taught with latest knowledge and keep pace with up to date information. Method: The study design was systematic review and it includes studies from databases of PUBMED, MEDLINE, Cochrane library, SCOPUS, Science direct, and Google scholar (2008-2019). The included studies were focusing on the effectiveness of blended learning on nursing students’ knowledge, skills and attitude and the studies that discussed about other methods of teaching and conducted on other specialty students were excluded. Result: The data was grouped and analyzed in terms of meta-analysis. Total 21 relevant articles were undertaken. Abstracted information is related to study design, population characteristics, intervention and outcomes. Conclusion: Blended learning as a teaching method is effective in improving the learning outcomes in terms of academic achievements and performance of nursing students regarding various topics/ procedures. Students also possess favorable attitude towards blended learning. Several studies came out with the conclusions that blended learning is beneficial in improving the learning outcomes.